The investment opportunity set and accounting procedure choice - Skinner, Douglas J. (Journal of Accounting and Economics, 1993)
This paper provides evidence on the cross-sectional relation between firms' investment opportunities, their debt and compensation contracts, their size and financial leverage, and their accounting procedure choices. This evidence is important, because previous studies hypothesize that the link between firms' investment opportunities and their accounting choices helps explain extant results on the size, debt/equity, and bonus plan hypotheses. However, while I find that firms' investment opportunities do affect the nature of their contracts. I also find that the ‘traditional’ explanations for accounting choice are important after controlling for the effects of the investment opportunity set.